THE ROLE OF THE TEACHER IN TEACHING SPEAKING - Haydarova, Ozoda Temurovna,; Juchkov, Juchkov Maksim Aleksandrovich (Журнал иностранных языков и лингвистики, 2023)
Students usually come to English classes with different attitudes and intentions. Some of them want to speak English as they hope that speaking English well will lead to a better job; so they have high motivation and they work very hard. However, many others may not understand why they should learn English or they learn it just to pass examination; so their motivation may be low. Therefore, it is very important for teachers to remember that and try to make lessons interesting and use varied activities to give students as much encouragement as possible. Teachers should know the characteristics of their learners and once they understand them they need to adapt their teaching in the following ways: